Experimental study on acoustic emission characteristics and damage-failure process of seawater sea-sand ultra-high-performance concrete under uniaxial compression - Tianyu Li; Yangtao Li; Tao Li; Xiamin Hu; Yuanhao Li; Jie Liao; Lidan Mei; Yuying Hou; Bokai Yang; Jinlong Gu (Case Studies in Construction Materials)
Seawater sea-sand ultra-high-performance concrete (SSUHPC) is a promising construction material with outstanding durability and service performance in marine environments. Further researches are needed to explore its mechanical and damage properties. This study investigates acoustic emission (AE) characteristics and damage-failure process of SSUHPC and freshwater river-sand UHPC (FRUHPC) under uniaxial compression. SSUHPC and FRUHPC specimens have undergone five years of sulfate corrosion, and were subjected to uniaxial compression tests until failure occurs. Stress-strain monitoring, AE technique, and digital image correlation (DIC) were employed during the tests, and a damage model were proposed for analysis. Results show that evolutions of AE signals, cracks, and maximum horizontal strain of SSUHPC have similar characteristics: first slowly increases, and then exhibit exponential growth when approaching failure. The established damage model can well describe the damage evolution and mechanical behavior of UHPC during loading. The damage evolution is mainly caused by tensile cracks, and the final failure shows large shear cracks, pull-out of steel fibers, and aggregate dislocation. Horizontal strain field obtained by DIC analysis can effectively characterize the damage process. Potential cracks may be identified when stress is at about 0.4 compressive strength, and damage zones rapidly expand 3–4 s before failure. The maximum horizontal strain exceeds 0.04, and width of strain localized region is 20–40 mm. By contrast, FRUHPC has better internal integrity and uniformity, causing higher compressive strength, more stable AE signals, and less damage during loading process. This work can provide reference for damage and failure characteristics of UHPC related materials.